Bladder cancer with pioglitazone: A case–control study. Issue 11 (November 2022) - Malhotra, Bhanu; Hiteshi, Priya; Khalkho, Persis; Malik, Ritu; Bhadada, Sanjay Kumar; Bhansali, Anil; Shafiq, Nusrat; Malhotra, Sameer; Kumar, Narendra; Rajput, Rajesh; Rastogi, Ashu
Abstract: Background: Varied reports suggest a contentious relationship of bladder malignancy with pioglitazone in patients with type 2 diabetes. Aim: To study an association (prevalence and predictors) of bladder malignancy with pioglitazone therapy in Asian-Indian type 2 diabetes patients. Method: In this observational multicenter study, type 2 diabetic patients attending out-patient diabetes-clinic were evaluated. A detailed history of anti-diabetic medication, dose, duration, pioglitazone usage, time since initiation of pioglitazone, physical examination, biochemical tests and details pertaining to prevalent neuropathy, retinopathy and nephropathy were recorded. Details of bladder cancer or any malignancy (if present), time since diagnosis, risk factors for bladder cancer and histopathology records were noted. The study cohort was divided into two groups-pioglitazone ever users (Group A) and never users (Group B). Results: A total of 8000 patients were screened out of which 1560 were excluded. Among 6440 included patients, 1056 (16.3%) patients were in group A and 5384 (83.6%) group B. Patients on pioglitazone were older (59.1 vs 57.7 years, p < 0.001), had longer duration of diabetes (12.7 vs 10.6 years, p < 0.001) with poor glycemic control (HbA1c 8.5 vs 8.3%, p < 0.01). A total of 74 patients had prevalent bladder cancer [16 (1.5%) in Group A and 58 in Group B (1.0%)]. Prevalent bladder cancer was not significantly greater in ever-users (odds ratio OR = 1.29, 95% confidence interval CI, 0.83–2.00) compared to never-users (odds ratio OR = 0.94, 95% confidence interval CI, 0.834–1.061) of pioglitazone (p = 0.207). However, history of hematuria in pioglitazone-users; while older age (>58 year), history of smoking and hematuria in the whole cohort were significant associated with bladder cancer. In the entire study cohort, 254 patients; 3.5% of males (128 out of 3575) and 4.6% of females (126 out of 2713) developed any malignancy. Age was significantly associated with prevalent malignancy in people with diabetes (odds ratio OR 1.036, 95% confidence interval CI: 1.022–1.051, p = 0.00) on multivariate forward regression. Conclusion: Pioglitazone use in Asian-Indians is not associated with an increased bladder cancer risk. However, pioglitazone should be restricted in individuals with history of hematuria. Age more than 58 years is a significant risk factor for development of any malignancy, particularly bladder cancer. Highlights: Glitazones are associated with bladder cancer despite reducing insulin resistance. Amongst 8000 diabetic individuals stratified by pioglitazone ever-use, no increased risk of bladder cancer was found. History of hematuria amongst pioglitazone-users was asoociated with bladder cancer. Age was significantly associated with prevalent any malignancy amongst people with diabetes.